Resolution of the City Council of the City of Oxnard Supporting the Purchase of Southern California Edison Company Property - Manuel M. Lopez:::Mayor, City of Oxnard::: (2000)
A resolution which discusses the acquisition of Southern California Edison Company Property for development purposes.